Foucault’s Adventure in Iran and His Last “Turn” - Reihanzadeh, Arsalan (Filozofski vestnik, 2023)
In light of the Iranian uprising of 1978–79, Foucault preferred to use the term revolt instead of revolution. In the first part of the article, we attempt to go beyond the limits of the nonspecific distinction he made between revolt and revolution by drawing on Furio Jesi’s phenomenology of revolt and showing in what sense the Iranian uprising can be considered a revolt. In the second part, the article highlights the connection between the Iranian uprising and Foucault’s later works by arguing that his adventure in Iran effectively shaped his final intellectual trajectory. By examining the tension between the transcendental and the historical in Foucault’s works, we propose to read his Iranian experience against the backdrop of such tension to better understand his different approach to the question of the transcendental in his final years.